Mechanistic insights into pincer-ligated palladium-catalyzed arylation of azoles with aryl Iodides: evidence of a Pd-II-Pd-IV-Pd-II pathway - Khake, Shrikant M.; Jagtap, Rahul A.; Dangat, Yuvraj B.; Gonnade, Rajesh G.; Vanka, Kumar; Punji, Benudhar (Organometallics, 2016)
Pincer-based (R2POCNR′2)PdCl complexes along with CuI cocatalyst catalyze the arylation of azoles with aryl iodides to give the 2-arylated azole products. Herein, we report an extensive mechanistic investigation for the direct arylation of azoles involving a well-defined and highly efficient (iPr2POCNEt2)PdCl (2a) catalyst, which emphasizes a rare PdII–PdIV–PdII redox catalytic pathway. Kinetic studies and deuterium labeling experiments indicate that the C–H bond cleavage on azoles occurs via two distinct routes in a reversible manner. Controlled reactivity of the catalyst 2a underlines the iodo derivative (iPr2POCNEt2)PdI (3a) to be the resting state of the catalyst. The intermediate species (iPr2POCNEt2)Pd-benzothiazolyl (4a) has been isolated and structurally characterized. A determination of reaction rates of compound 4a with electronically different aryl iodides has revealed the kinetic significance of the oxidative addition of the C(sp2)–X electrophile, aryl iodide, to complex 4a. Furthermore, the reactivity behavior of 4a suggests that the arylation of benzothiazole proceeds via an oxidative addition/reductive elimination pathway involving a (iPr2POCNEt2)PdIV(benzothiazolyl)(Ar)I species, which is strongly supported by DFT calculations.

Unified strategy for nickel-catalyzed C-2 Alkylation of indoles through chelation assistance - Soni, Vineeta; Jagtap, Rahul A.; Gonnade, Rajesh G.; Punji, Benudhar (ACS Catalysis, 2016)
A nickel-catalyzed direct C-2 alkylation of indoles through monodentate-chelation assistance has been described. This reaction proceeds via an unusual strategy by the use of a well-designed and defined (quinolinyl)amido–nickel catalyst, [{κN,κN,κN-Et2NCH2C(O)(μ-N)C9H6N}Ni(OAc)], providing a solution to the limitations associated with bidentate-chelate auxiliaries. The method allows coupling of indoles with various unactivated primary and secondary alkyl halides with ample substrate scope. This uniquely strategized alkylation proceeded through crucial C–H activation and via an alkyl radical intermediate. The reaction by this approach represents a rare example of Ni-catalyzed monodentate-chelate-assisted C–H functionalization.

Expeditious and solvent-free nickel-catalyzed C−H arylation of arenes and indoles - Jagtap, Rahul A.; Soni, Vineeta; Punji, Benudhar (ChemSusChem, 2017)
An efficient solvent-free nickel-catalyzed method for C−H bond arylation of arenes and indoles has been developed, which proceeds expeditiously through chelation assistance. The reaction is highly selective for mono-arylation and tolerates sensitive and structurally diverse functionalities, such as halides, ethers, amines, indole, pyrrole and carbazole. This reaction represents the first example of a nickel-catalyzed C−H arylation by monochelate assistance and symbolizes a rare precedent in solvent-free C−H arylation. Mechanistic investigations by various controlled reactions, kinetic studies, and deuterium labeling experiments suggest that the arylation follows a single electron transfer (SET) pathway involving the turnover-limiting C−H nickelation process.

C-H functionalization of indoles by 3d transition-metal catalysis - Jagtap, Rahul A.; Punji, Benudhar (Asian Journal of Organic Chemistry, 2019)
Over the past decade, the use of 3d transition metal for the regioselective C-H bond functionalization of indoles has significantly increased. Particularly, advances in manganese, iron, cobalt, nickel and copper catalysis have demonstrated the selective C(2)-H and C(3)-H arylation, alkenylation, alkynylation and alkylation to a greater extent. Similarly, the C-O and C-N bond-forming reactions are manifested via direct C-H bond activation by these earth-abundant metals. The emergence of 3d metals in selective functionalization of the biologically relevant indoles and related heteroarenes would make this protocol more attractive for practical applications. Herein, we provide a brief overview of 3d transition metal-catalyzed (mostly Mn, Fe, Co, Ni and Cu) C-H functionalization of indoles and related heteroarenes.
Keywords: 3d transition metal; C-H functionalization; Indole; indoline

Nickel-catalyzed straightforward and regioselective C-H alkenylation of indoles with alkenyl bromides: scope and mechanistic aspect - Jagtap, Rahul A.; Vinod, C. P.; Punji, Benudhar (ACS Catalysis, 2019)
Nickel-catalyzed regioselective C-H bond alkenylation of indoles and related heteroarenes with alkenyl bromides is accomplished under relatively mild conditions. This method allows the straightforward synthesis of C-2 alkenylated indoles employing an air-stable and well-defined nickel catalyst, (bpy)NiBr2, providing a solution to the limitations associated with hydroindolation and oxidative alkenylation. The reaction conceded the coupling of indole derivatives with various alkenyl bromides, such as aromatic and heteroaromatics, alpha- and beta-substituted as well as exo- and endo-cyclic alkenyl compounds. An extensive mechanistic investigation, including controlled study, reactivity experiments, kinetics and labeling studies, and EPR and XPS analyses, highlights that the alkenylation proceeds through a single-electron transfer process comprising an odd-electron oxidative addition of alkenyl bromide. Furthermore, the alkenylation operates via a probable Ni(I)/Ni(III) pathway involving the rate-limiting C-H nickelation of indole.
Keywords: alkenylation; C-H activation; indoles; Mechanism; Nickel; single-electron transfer

Scope and mechanistic aspect of nickel-catalyzed alkenylation of benzothiazoles and related azoles with styryl bromides - Patel, Ulhas N.; Jagtap, Rahul A.; Punji, Benudhar (Organometallics, 2019)
Alkenylation of benzothiazoles and related azoles with alkenyl bromides is achieved employing the well-defined and air-stable nickel complexes, (bpy)NiBr2 and [Ni(bpy)(3)] [NiBr4], as catalysts. Numerous electronically distinct alkenyl bromides efficiently coupled with substituted benzothiazoles, oxazoles, and benzimidazoles under the catalytic conditions to afford 2-alkenylated azoles. An extensive mechanistic study of the alkenylation of benzothiazole using (bpy)NiBr2 highlights a single-electron transfer process for the reaction involving the two-step one-electron oxidative addition of alkenyl bromide. The substrate benzothiazole plays a significant and diverse role in the reaction, and C-H bond cleavage is reversible in nature. Detailed kinetic analysis and control reactivity studies are indicative of a Ni(I)/Ni(III) pathway for the alkenylation comprising the rate-influencing reductive elimination step.

Expeditious and solvent-free nickel-catalyzed c-h arylation of arenes and indoles (vol 10, pg 2242, 2017) - Jagtap, Rahul A.; Soni, Vineeta; Punji, Benudhar (ChemSusChem, 2020)
Keywords: Arylation; C-H activation; heterocycles; Homogeneous catalysis; Nickel

Iron-catalyzed C(sp(2))-H alkylation of indolines and benzo[h]quinoline with unactivated alkyl chlorides through chelation assistance - Jagtap, Rahul A.; Samal, Pragnya Paramita; Vinod, C. P.; Krishnamurty, Sailaja; Punji, Benudhar (ACS Catalysis, 2020)
Regioselective C-H bond alkylation of indolines and benzo[h]quinoline with a wide range of unactivated and highly demanded primary and secondary alkyl chlorides is accomplished using a low-cost iron catalyst. This reaction tolerates diverse functionalities, such as C(sp(2))-Cl, fluoro, alkenyl, silyl, ether, thioether, pyrrolyl, and carbazolyl groups including cyclic and acyclic alkyls as well as alkyl-bearing fatty-alcohol and polycyclic-steroid moieties. The demonstrated iron-catalyzed protocol proceeded via either a five-membered or a six-membered metallacycle. Intriguingly, the C-7-alkylated indolines can be readily functionalized into free-NH indolines/indoles and tryptamine derivatives. A detailed mechanistic investigation highlights the participation of an active Fe(I) catalyst and the involvement of a halogen-atom transfer process via a single-electron-based mechanism. Deuterium labeling and kinetics analysis indicate that the C-H metalation of indoline is the probable turnover-limiting step. Overall, the experimental and theoretical studies supported an Fe(I)/Fe(III) pathway for the alkylation reaction comprising the two-step, one-electron oxidative addition of alkyl chloride.
Keywords: alkyl chlorides; Alkylation; C-H activation; chelation assistance; indolines; iron

MnBr2-catalyzed direct and site-selective alkylation of indoles and benzo[h]quinoline - Jagtap, Rahul A.; Verma, Suryadev K.; Punji, Benudhar (Organic Letters, 2020)
Manganese-catalyzed regioselective C-H alkylation of indoles and benzo[h]quinoline with a variety of unactivated alkyl iodides is reported. Unlike other Mn-catalyzed C-H functionalization, this protocol does not require a Grignard reagent base and employs a simple and inexpensive MnBr2 as a catalyst. This method tolerates diverse functionalities, including fluoro, chloro, bromo, iodo, alkenyl, alkynyl, pyrrolyl, and carbazolyl groups. The alkylation proceeds through a single-electron transfer pathway comprising reversible C-H manganesation and involving an alkyl radical intermediate.

Achiral and chiral NNN-pincer nickel complexes with oxazolinyl backbones: application in transfer hydrogenation of ketones - Jagtap, Rahul A.; Ankade, Shidheshwar B.; Gonnade, Rajesh G.; Punji, Benudhar (New Journal of Chemistry, 2021)
We describe the synthesis of new NNN-oxazolinyl-pincer nickel complexes and their application in the transfer hydrogenation of ketones. Achiral NNN-ligands, R `(2)-oxazolinyl-2-C6H4-NH-C(O)CH2NEt2 [((R ` 2-OxNNNEt2))-H; R' = H (3a), R ` = Me (3b)], and chiral ligands, (R)-R `-oxazolinyl-2-C6H4-NH-C(O)CH2NEt2 [(R)-((R `-OxNNNEt2))-H; R ` = Ph (3c), R ` = CH2Ph (3d), R ` = Pr-i (3e), R ` = (CH2Pr)-Pr-i (3f)], were efficiently synthesized. Treatment of these ligands with (DME)NiCl2 afforded the desired amido-pincer nickel complexes, ((R ` 2-OxNNNEt2))NiCl [R ` = H (4a), R ` = Me (4b)] and ((R `-OxNNNEt2))NiCl [R ` = Ph (4c), R ` = CH2Ph (4d), R ` = Pr-i (4e), R ` = (CH2Pr)-Pr-i (4f)], in good yields. All the ligand precursors and nickel complexes were thoroughly characterized by various analytical techniques. The molecular structures of 4a, 4d and 4f were established by X-ray crystallography. The developed nickel complexes were found to be efficient catalysts for the transfer hydrogenation of ketones using (PrOH)-Pr-i as a viable hydrogen source. Enantioselectivity in hydrogenation was not observed with the developed chiral catalysts.

Nickel-catalyzed C-H bond functionalization of azoles and indoles - Jagtap, Rahul A.; Punji, Benudhar (Chemical Record, 2021)
Direct C-H functionalization of privileged and biologically relevant azoles and indoles represents an important chemical transformation in molecular science. Despite significant progress in the palladium-catalyzed regioselective C-H functionalization of azoles and indoles, the use of abundant and less expensive nickel catalyst is underdeveloped. In the recent past, the nickel-catalyzed regioselective C-H alkylation, arylation, alkenylation and alkynylation of azoles and indoles have been substantially explored, which can be applied to the complex organic molecule synthesis. In this Account, we summarize the developments in nickel-catalyzed regioselective functionalization of azoles and indoles with a considerable focus on the reaction mechanism.
Keywords: azoles; C-C Bond formation; C-H functionalization; indoles; Nickel

Efficient route to 3,3 `-biindolinylidene-diones by iron-catalyzed dimerization of isatins - Jagtap, Rahul A.; Pradhan, Chandini; Gonnade, Rajesh G.; Punji, Benudhar (Chemistry-an Asian Journal, 2022)
Iron-catalyzed dimerization of various isatin derivatives is described for the efficient synthesis of 3,3 `-biindolinylidene-diones (isoindigos). The reaction provides easy access to self-coupled and cross-coupled 3,3 `-indolinylidene-diones that have high relevance to biology and materials. This Fe(0)- or Fe(II)-catalyzed dimerization reaction tolerates a wide range of functionalities, such as fluoro, chloro, bromo, alkenyl, nitrile, ether, ester, pyrrolyl, indolyl and carbazolyl groups, including cyclic and acyclic alkyls as well as an alkyl-bearing fatty-alcohol moiety. Especially, the coupling between two distinct isatins provided excellent selectivity for the cross-dimerization with trace of self-couplings. The single-crystal X-ray diffraction study established the molecular structure of eight dimerized products. A preliminary mechanistic study of the Fe-catalyzed dimerization supported the radical pathway for the reaction.
Keywords: Cross-coupling; dimerization; iron; Isatin; Isoindigo; Mechanism

Iron-catalyzed regioselective C-H alkylation of indoles: an additive-free approach in renewable solvent - Pradhan, Chandini; Jagtap, Rahul A.; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Punji, Benudhar (Green Chemistry, 2023)
Alkylated indoles are important motifs in various biologically active molecules and drug candidates. Herein, we report a mild and efficient iron-catalyzed protocol for synthesizing alkylated indoles via C-H bond alkylation of indoles with unactivated alkenes, demonstrating a high level of regioselectivity. The reaction occurs under additive-free, solvent-free (or trace green solvent, 2-MeTHF) and less energy-intensive conditions using a sustainable metal catalyst and provides easy access to privileged alkylated indoles with anti-Markovnikov selectivity. Alkylation is compatible with important functionalities, such as fluoro, chloro, trifluoromethyl, alkenyl, ether, thioether, silyl, and siloxane, including heteroaryl, pyridinyl, carbazolyl, and indolyl moieties (45 examples, up to 96% yield). The developed protocol is very simple, straightforward, and fully accords with the principles of green chemistry. A detailed mechanistic investigation manifests the facile indole's C-H activation at the Fe(0) center, reversible 1,2-insertion of the alkene into the Fe-H bond of a metallacycle, and a turnover-limiting reductive elimination. Alkylated indoles are important motifs in various biologically active molecules and drug candidates.
Keywords: Aromatic Ketones; Green; organic synthesis